Myths, legends, and heroes : essays on Old Norse and Old English literature in honour of John McKinnell - McKinnell, John; Anlezark, Daniel (Toronto Old Norse and Icelandic studies., 2011)
In Myths, Legends, and Heroes, editor Daniel Anzelark has brought together scholars of Old Norse-Icelandic and Old English literature to explore the translation and transmission of Norse myth, the use of literature in society and authorial self-reflection, the place of myth in the expression of family relationships, and recurrent motifs in Northern literature.The essays in Myths, Legends, and Heroes include an examination of the theme of sibling rivalry, an analysis of Christ's unusual ride into hell as found in both Old Norse and Old English, a discussion of Beowulf's swimming prowess and an analysis of the poetry in Snorri Sturluson's Edda. A tribute to Durham University professor John McKinnell's distinguished contributions to the field, this volume offers new insights in light of linguistic and archaeological evidence and a broad range of study with regard to both chronology and methodology.